Ocular Manifestations of the Sturge–Weber Syndrome - Kiana Hassanpour; Ramin Nourinia; Ebrahim Gerami; Ghavam Mahmoudi; Hamed Esfandiari (Journal of Ophthalmic & Vision Research)
Abstract Sturge–Weber syndrome (SWS) or encephalotrigeminal angiomatosis is a non-inherited congenital disorder characterized by neurologic, skin, and ocular abnormalities. A somatic activating mutation (R183Q) in the GNAQ gene during early embryogenesis has been recently recognized as the etiology of vascular abnormalities in SWS. Approximately, half of the patients with SWS manifest ocular involvement including glaucoma as the most common ocular abnormality followed by choroidal hemangioma (CH). The underlying pathophysiology of glaucoma in SWS has not been completely understood yet. Early onset glaucoma comprising 60% of SWS glaucoma have lower success rates after medical and surgical treatments compared with primary congenital glaucoma. Primary angle surgery is associated with modest success in the early onset SWS glaucoma while the success rate significantly decreases in late onset glaucoma. Filtration surgery is associated with a higher risk of intraoperative and postoperative choroidal effusion and suprachoroidal hemorrhage. CH is reported in 40–50% of SWS patients. The goal of treatment in patients with CH is to induce involution of the hemangioma, with reduction of subretinal and intraretinal fluid and minimal damage to the neurosensory retina. The decision for treating diffuse CHs highly depends on the patient's visual acuity, the need for glaucoma surgery, the presence of subretinal fluid (SRF), its chronicity, and the potential for visual recovery.